Germany : Financial Sector Assessment Program-Detailed Assessment of Observance on the Eurex Clearing AG Observance of the CPSS-IOSCO Principles for Financial Market Infrastructures. (IMF Staff Country Reports; Country Report ;, 2016)
This paper provides a detailed assessment of observance on the Eurex Clearing AG observance of the Committee on Payment and Settlement Systems-International Organization of Securities Commissions principles for financial market infrastructures. Eurex Clearing is a global central counterparty clearing house that clears a broad range of both listed and over-the-counter (OTC) products. It offers fully automated and straight-through post trade services to the derivatives markets Eurex Deutschland and Eurex Zurich, the Frankfurt Stock Exchange, the multilateral trading systems of Eurex Bonds GmbH and Eurex Repo GmbH, the Irish Stock Exchange as well as clearing services for OTC interest rate derivatives (Eurex OTC Clear), as well as clearing services for transactions in cash equities, bonds, repos, derivatives, secure funding, securities financing, and transactions.